Investigation of the Performances of a Diesel Engine Operating on Blended and Emulsified Biofuels from Rapeseed Oil - Vladimir Anatolyevich Markov; Bowen Sa; Sergey Nikolaevich Devyanin; Anatoly Anatolyevich Zherdev; Pablo Ramon Vallejo Maldonado; Sergey Anatolyevich Zykov; Aleksandr Dmitrievich Denisov; Hewage Chithral Ambawatte (Energies, 2021)
The article discusses the possibility of using blended biofuels from rapeseed oil (RO) as fuel for a diesel engine. RO blended diesel fuel (DF) and emulsified multicomponent biofuels have been investigated. Fuel physicochemical properties have been analyzed. Experimental tests of a diesel engine D-245 in the operating conditions of the external characteristic curve and the 13-mode test cycle have been conducted to investigate the effect of these fuels on engine performances. CFD simulations of the nozzle inner flow were performed for DF and ethanol-emulsified RO. The possibility of a significant improvement in brake thermal efficiency of the engine has been noted. The efficiency of using blended biofuels from RO as a motor fuel for diesel engines has been evaluated based on the experimental test results. It was shown that in comparison with the presence of RO in emulsified multicomponent biofuel, the presence of water has a more significant effect on NOx emission reduction. The content of RO and the content of water in the investigated emulsified fuels have a comparable influence on exhaust smoke reduction. Nozzle inner flow simulations show that the emulsification of RO changes its flow behaviors and cavitation regime.